Reduced Graphene Oxide/Silica Based Electrode Material: Synthesis and Characterization - Sinta Nur Mazida Rafiq; Dina Rahmawati; Mukhtar Effendi; Sib Krishna Ghoshal; Candra Kurniawan; Wahyu Widanarto (Department of Physics, Sebelas Maret University, 2024)
Developing a Reduced Graphene Oxide (rGO) synthesis method based on rice husk as a composite electrode material with silica has garnered particular attention for designing high-quality electrode materials. This research successfully synthesized rGO-Si material from rice husk-derived activated carbon through a one-step thermal reduction process at 200 °C. This method offers a simple, efficient, cost-effective, and environmentally friendly synthesis approach. The resulting samples' morphology, surface composition, crystal structure, surface area, and pore diameter size were characterized using FE-SEM, EDX, XRD, and SAA-BET. EDX characterization results confirmed the predominance of carbon content in the samples. At the same time, the natural emergence of Si without external addition due to thermal reduction at 200 °C was an intriguing initial finding. The spherical crystal structure of silica between the wrinkled rGO layers was confirmed through FE-SEM and XRD analysis. The synergistic effect between Si and rGO significantly increased the sample's surface area, with a value of 34.17 m2/g for the rGO sample before thermal reduction, which increased to 121.24 m2/g after the thermal reduction process at 200 °C. This process also positively impacted the reduction in pore size of rGO-Si, with a value decreasing from 9.33 nm before thermal reduction to 4.89 nm after the thermal reduction process. The results of this study demonstrate that rGO-Si synthesized from rice husk-derived activated carbon holds great potential as a high-performance electrode material, combining the advantages of thermal reduction, natural Si content, and increased surface area for diverse applications.